The Complementarity of Language and Other Human Capital: Immigrant Earnings in Canada - Barry R. Chiswick; Paul W. Miller (Institute for the Study of Labor (IZA), 2002)
This paper analyzes the effects of language practice on earnings among adult male immigrants in Canada using the 1991 Census. Earnings are shown to increase with schooling, pre-immigration experience and duration in Canada, as well as with proficiency in the official languages (English and French). Using selectivity correction techniques, it is shown that there is complementarity between language skills and both schooling and preimmigration experience. That is, greater proficiency in the official languages enhances the effects on earnings of schooling and pre-immigration labor market experience. Language proficiency and post-migration experience appear to be substitutes, that is, those with greater proficiency have a smaller effect of time in Canada on earnings.
Keywords: J61; J31; J24; I21; 330; Immigrants; human capital; language skills; schooling; earnings; Canada; Migranten; Einkommen; Humankapital; Sprache; Bildungsertrag; Schätzung; Kanada